A new species of Palpita Hübner from Laos (Lepidoptera, Crambidae, Spilomelinae) - Ko, Jae-Ho; Bayarsaikhan, Ulziijargal; Lee, Tak-Gi; Cha, Yeong-Bin; Lee, Jong Koo; Bae, Yang-Seop (Zootaxa, 2021)
A new species of the genus Palpita Hübner is described from Laos, which is very close to P. inusitata (Butler, 1879) found in Japan.